2022
DOI: 10.3389/fevo.2022.857317
|View full text |Cite
|
Sign up to set email alerts
|

Animal Coloration in the Anthropocene

Abstract: Natural habitats are increasingly affected by anthropogenically driven environmental changes resulting from habitat destruction, chemical and light pollution, and climate change. Organisms inhabiting such habitats are faced with novel disturbances that can alter their modes of signaling. Coloration is one such sensory modality whose production, perception and function is being affected by human-induced disturbances. Animals that acquire pigment derivatives through diet are adversely impacted by the introductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 147 publications
0
5
0
Order By: Relevance
“…This study examined the influence of anthropogenic pollution on an important signalling modality in birds – the expression of colourful signals (Koneru & Caro, 2022). Analysing 421 effect sizes from 59 studies, we found evidence suggesting a negative impact of pollution on the expression of colour traits, consistent with the hypothesis proposed by Hill (1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study examined the influence of anthropogenic pollution on an important signalling modality in birds – the expression of colourful signals (Koneru & Caro, 2022). Analysing 421 effect sizes from 59 studies, we found evidence suggesting a negative impact of pollution on the expression of colour traits, consistent with the hypothesis proposed by Hill (1995).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of anthropogenic pollutants and urbanisation on avian colouration has been addressed previously in several narrative reviews. Koneru & Caro (2022) provided a comprehensive overview of animal colouration in the Anthropocene, including signal transmission and perception in altered habitats and the consequences of climate change for colour trait expression. Lifshitz & St Clair (2016) summarised current knowledge on colour ornaments as potential bioindicators, and Peneaux et al (2021a) considered the effects of pollutants on carotenoid-based colouration and provided guidelines for the use of colour signals as bioindicators.…”
Section: Introductionmentioning
confidence: 99%
“…However, these interactions vary over time and space since colours can perform their functions and be perceived by animals in different ways, depending on environmental conditions (Endler 1990), resulting in several biotic and abiotic factors competing with each other and acting as selective pressures on colours (Endler 1992;Postema et al 2023). Unfortunately, colour also re ects the impacts of environmental degradation caused by anthropogenic actions (Spaniol et al 2020; Koneru and Caro 2022;López-Idiáquez et al 2022) in abiotic characteristics of environments, affecting the e ciency of their functions (Endler 1978;Burtt 1981), with reported cases ranging from changes in speci c species (Cook 2003) to whole communities in environments such as tropical forests (Spaniol et al 2020) and marine environments (Coker et However, only one study seems to have evaluated quantitative butter y colour (diversity, brightness, hue and saturation) responses to anthropogenic actions (Spaniol et al 2020). Treating colours as functional traits and using them as indicators for deforestation impacts in the Amazon Rainforest, we have shown a loss of colouration diversity with increasing habitat disturbance, in which forest fragmentation and deforestation strongly affect colour traits, with butter ies less colourful in areas of early succession and forest fragments; in the former areas, they also had higher saturation and a red hue but lower brightness, indicating the predominance of camou age as a strategy.…”
Section: )mentioning
confidence: 99%
“…Animal colouration plays a functional role associated with distinct aspects of organismal natural history, ranging from intra- (Rowland 2018) to interspeci c communication (Caro and Allen 2017), in which there seems to be a direct and positive association between species biodiversity and colour diversity (Koneru and Caro 2022) since environments with different landscapes and species compositions can lead lineages to acquire different strategies involving this trait (Adams et al 2014). Body colours end up mediating communication and interactions between animals and other organisms and with the surrounding environment (Cuthill et al 2017).…”
Section: )mentioning
confidence: 99%
“…Stickleback males reduce their investment in their ornament, red nuptial coloration, when visibility deteriorates ( Candolin et al 2016 ), but across species the pattern varies; some species adjust their ornaments to visibility, such as the brown trout Salmo trutta ( Eaton and Sloman 2011 ) and the western rainbowfish Melanotaenia australis ( Kelley et al 2012 ), whereas others do not, such as the pipefish Nerophis ophidion ( Sundin et al 2016 ). These differences in responses are probably related to temporal and spatial variation in visibility and the evolutionary history of the species, which has determined the evolution of reaction norms for plastic responses ( Chevin and Hoffmann 2017 ; Candolin 2019 ; Koneru and Caro 2022 ). The responses may be adaptive or not, depending on how they influence the costs and benefit of ornamentation.…”
Section: Introductionmentioning
confidence: 99%